Verkehrsphasenbasierte Datenanalyse von zeitlich-räumlichen Strukturen der Staufronten - Molzahn, Sven-Eric (Schriftenreihe / Institut für Verkehrswesen, Karlsruher Institut für Technologie, 2022)
To this day, the sudden emergence of the structures of congested traffic poses a great danger to drivers and vehicles: This is especially true when driving into the end of a traffic jam. One way to reduce the danger is the timely and precise warning of the end of a traffic jam. This paper presents a method to determine and classify the hazard potential at the end of a traffic jam by means of empirical microscopic traffic data.